An assessment of surgical outcome with the influencing factors of horizontal strabismus surgery - Pandey, Saraswati; Pandey, Araniko; Bajracharya, Kabindra; Thapa, Hari B; Shrestha, Shakti; Bhari, Arjun M; Rai, Salma KC (Asian Journal of Medical Sciences, 2017)
Background: Influencing factors of conventional horizontal surgery for surgical outcome has not been assessed in Nepal. Aims and Objective: To assess the pre-operative factors that influences the surgical outcome of horizontal strabismus surgery. Materials and Methods: The medical records of 68 patients who underwent their first horizontal strabismus surgery at Lumbini Eye Institute from 1st January to 30th December 2015 were retrospectively reviewed. The collected clinical data included diagnosis, age group, visual acuity, binocular function, extraocular motility and pre and postoperative deviation. The success of surgery was defined by eye deviation less than 10 prism diopters (PD) at 6 weeks after operation. The influencing factors for surgical success (diagnosis, age group, visual acuity, binocular function, and angle deviations) were analyzed using chi square test and Mann-Whitney - U test, where ever appropriate. Results: Out of 113 patients who underwent strabismus surgery during the year, 68 patients were enrolled in the study. Majority of the patients (27, 39.7%) were >9 years of age and 52.9% were female. Thirty seven patients (54.4%) were esotropic whereas, 31 were exotropic. Preoperatively, angle of deviation ranged from 20 to 90 PD with binocular vision present in 57.4% cases. Overall, success was seen in 26 patients (38.2%). Pre-operative angle of deviation and binocular vision had statistical significance with surgical success (p = 0.012 and 0.026 respectively). Conclusion: Larger angle of deviation and poor binocular vision at presentation has higher failure rate for horizontal strabismus surgery. Asian Journal of Medical Sciences Vol.8(5) 2017 54-57